TANGGUNG JAWAB KEPEMIMPINAN KRISTEN DALAM KONSEP IMAGO DEI DI GEREJA METODIS INJILI SURABAYA DAN MALANG: Indonesia - Mintoni Asmo Tobing; Yatmini Yatmini; Kamenia Melyanti Nabuasa (Manna Rafflesia, 2025)
The implementation of Christian leadership responsibilities in church organizations tends to imitate a secular leadership style built on a philosophical basis. Indeed, Christian leadership has to be based on biblical principles. Secular leadership shows negative aspects, such as authoritarianism, materialisticism, and conflict management. Therefore, this study aims to provide an understanding of the basis for the implementation of Christian leadership responsibilities based on the imago Dei concept as God's original purpose in creation. In its implementation, humans not only inherit God's attributes but also represent God in leadership responsibilities. This qualitative study used a phenomenological approach. The findings indicate that leadership responsibilities in the Evangelical Methodist Church environment have been implemented but have not been built based on the imago Dei concept. Thus, this study provides a new perspective that leadership built based on the imago Dei concept affects the implementation of leadership responsibilities without any influence of changes in the times.